Responses to Pandemic Covid-19 by Mosque-Based Zakat Agency: Opportunities and Limitations in Zakat Management - Ansoriyah, Faizatul; Warella, Y; Purnaweni, Hartuti; Hastuti, Retno Sunu (DINIKA : Academic Journal of Islamic Studies, 2020)
Pandemics not only have health effects, but also social and economic ones. Zakat plays a significant role in poverty alleviation and in disaster mitigation, including the impacts caused by the current pandemic. Unit Pengumpul Zakat or The Zakat Management Unit at Mosque (UPZ Masjid) is the smallest and closest zakat management to the community. This article tries to discover the opportunities and challenges faced by zakat management in mosques in overcoming the impact of the Covid-19 pandemic. Management of zakat in mosques with a localization system is in line with fiqh zakat guidelines and the provisions of Law No. 23 of 2011. Using mixed method studies, the research shows that localization of zakat management has a great opportunity in maximizing the role of UPZ in helping people deal with the pandemic-affected communities. The results of this study show that the role of UPZ only occurs during fasting month and besides, the use of zakat mal has not yet been optimized. There are reasons why UPZ does not operate optimally, including the lack of skill training from BAZNAS and the absence of reporting and activity monitoring.